PMM.39 Evaluating the effectiveness of a leaflet educating women on obesity and pregnancy. Are we intervening pre-pregnancy fulfilling the new Centre for Maternal and Child Enquiries (CMACE) recommendation?. (9th June 2014) - Ng, KYB; Mohamed, S; Sagoo, B; Mulki, O; Hamid, R
Abstract : The prevalence of maternal obesity has increased to 16–19% in the early 2000s; it is one of the most common risk factors for maternal and fetal morbidity and mortality. About 50% of women who died were obese as reported by the last two 'Saving Mothers' Lives Reports' in 2007 1 and 2011. 2 RCOG and CMACE guidelines recommend that all obese women of child bearing age should be counselled pre-pregnancy and supported throughout their pregnancy to improve maternal and fetal outcomes. 3 Although such guidelines are present, there is uncertainty if this information is understood and accessible pre-pregnancy. Because of the high obesity population in our local area (27%), a leaflet has been produced to educate women of the risks and how they can be minimised pre- and during- pregnancy. It also contains information about antenatal appointments and what they should expect at each visit. Pregnant women with a BMI ≥30 attending our Obstetrics Department were given the leaflet. Following this, a questionnaire assessed their insights into risks associated with obesity in pregnancy, the importance of lifestyle changes, their motivation for change, their understanding of the leaflet and whether this information was provided pre-pregnancy. Preliminarily, we found that the majority of women received little or no pre-pregnancy counselling or advice regarding obesity and its risks. Women felt that they would have benefited from this leaflet in their local community prior to getting pregnant so that they could have acted upon its recommendations hence fulfilling the CMACE guidelines and improving quality of care. References: The Confidential Enquiry into Maternal and Child Health (CEMACH). Saving Mothers' Lives: reviewing maternal deaths to make motherhood safer (2003–2005). 2007 Centre for Maternal and Child Enquiries (CMACE). Saving mothers' lives. Reviewing maternal deaths to make motherhood safer: 2006–2008. BJOG . 2011 Oct;118(11):1402–3; discussion 3–4 Royal College of Obstetricians and Gynaecologists (RCOG), Centre for Maternal and Child Enquiries (CMACE). CMACE/RCOG Joint Guideline: Management of Women with Obesity in Pregnancy. 2010